Modelling beach morphological changes during episodic erosion-recovery events: preliminary results - Oliveira, F. S. B. F. (2014)
Episodic and seasonal beach-dune system erosion, unlike long-term erosion, are, in general, followed by natural beach-dune recovery. This study, developed based on numerical modelling, is focused on the wind driven waves onshore and offshore induced sediment fluxes and resulting beach-dune morphological evolution, particularly on the underlying physics not yet fully understood, during episodic events of erosion-recovery. The objective is to improve the prediction capacity of the short to medium-term morphodynamic numerical model XBeach, particularly in what concerns the beach recovery phenomenon, and thus contribute to its credible application.